2008
DOI: 10.1007/s11999-008-0296-2
|View full text |Cite
|
Sign up to set email alerts
|

Streamlining the Evaluation of Low Back Pain in Children

Abstract: The workup of low back pain in children often results in overimaging so as not to miss organic back pain. The primary goal of this study was to identify which combination of imaging modalities provides the most sensitive and specific screening protocol for children with low back pain. Medical records from 100 consecutive patients between 2 and 18 years of age presenting with low back pain, without night pain or constitutional symptoms, were evaluated. A hyperextension test combined with a radiograph showed a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…In this study, 78% of patients had no definitive final diagnosis, including those with disorders that might have been treatable but were not identified. Similarly, Auerbach et al 19 found a high prevalence of mechanical back pain (53%) with negative findings on radiographs, SPECT, CT, and MR imaging.…”
Section: Epidemiologymentioning
confidence: 86%
See 4 more Smart Citations
“…In this study, 78% of patients had no definitive final diagnosis, including those with disorders that might have been treatable but were not identified. Similarly, Auerbach et al 19 found a high prevalence of mechanical back pain (53%) with negative findings on radiographs, SPECT, CT, and MR imaging.…”
Section: Epidemiologymentioning
confidence: 86%
“…31 Radionuclide imaging can detect abnormalities (eg, spondylolysis, stress frac- 32 or bone lesions (eg, osteoid osteoma). In a study by Auerbach et al, 19 negative findings on a SPECT scan were 100% predictive of MBP in patients with Ͻ6 weeks of pain. MBP was diagnosed when there was no demonstrable cause of back pain and findings on all imaging studies (SPECT, CT, MR imaging) were negative.…”
Section: Nuclear Medicine Ct and Mr Imagingmentioning
confidence: 92%
See 3 more Smart Citations